1979
DOI: 10.1111/j.1365-2842.1979.tb00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Bite force and oral function in complete denture wearers

Abstract: Oral function was evaluated in complete denture wearers by using a questionnaire, clinical examination and bite force measurements. Ten patients with satisifactory and ten with unsatisfactory dentures were studied and six of the latter patients were reexamined 1 year after the insertion of new dentures. The bite force values were compared with those obtained in ten dentate controls. No significant differences in bite force were found between the satisfactory and unsatisfactory denture groups. Individual values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
1
21

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(114 citation statements)
references
References 11 publications
(15 reference statements)
10
82
1
21
Order By: Relevance
“…The previous studies with varied measuring methods indicated that maximal bite force was 5-6 times greater in the dentate subjects than in the denture wearers. 32 It suggested directly that stronger occlusal force needs natural teeth supported with periodontal tissue, and artificial teeth over mucous membrane of residual ridge is not sufficient for the recovery of bite force. In addition, it suggested indirectly that occlusal contacts between maxillary and mandibular teeth activate oral function by masticatory muscles and temporomandibular joints, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies with varied measuring methods indicated that maximal bite force was 5-6 times greater in the dentate subjects than in the denture wearers. 32 It suggested directly that stronger occlusal force needs natural teeth supported with periodontal tissue, and artificial teeth over mucous membrane of residual ridge is not sufficient for the recovery of bite force. In addition, it suggested indirectly that occlusal contacts between maxillary and mandibular teeth activate oral function by masticatory muscles and temporomandibular joints, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Prosthodontic literature and teaching presuppose that there is a close connection between the quality of dentures and the functional capacity but not all studies have been able to verify this (Haraldson, Karlsson & Carlsson, 1979;Laine, 1982). It is well known from clinical experience that there is a group of edentulous persons who have severe difficulties adapting to complete dentures, even if the technical quality of the dentures is high.…”
Section: Introductionmentioning
confidence: 92%
“…Under these conditions, all mandibular dentures were axially loaded with 10 kgf (98 N). Maximum bite force for denture wearers ranges between 7.03 kgf (69 N) and 14.57 kgf (142.9 N) according to previous studies [21][22][23].…”
Section: Methodsmentioning
confidence: 99%